The evolution of arch surgery: Frozen elephant trunk or conventional elephant trunk? - Moula, Amalia I.; Romeo, Jamie L. R.; Parise, Gianmarco; Parise, Orlando; Maessen, Jos G.; Natour, Ehsan; Bidar, Elham; Gelsomino, Sandro (Frontiers in Cardiovascular Medicine, 2022)
Treatment of aortic arch aneurysms and dissections require highly complex surgical procedures with devastating complications and mortality rates. Currently, repair of the complete arch until the proximal descending thoracic aorta consists of a two-stage procedure, called elephant trunk (ET) technique, or a single stage a single-stage technique referred to as frozen elephant trunk (FET). There is conflicting evidence about the perioperative results of ET in comparison with FET. We carried out a meta-analysis to investigate possible differences in perioperative and early (up to 30 days) outcomes of ET versus FET, particularly for mortality, spinal cord injury (SCI), stroke, and renal failure. We also performed a meta-regression to explore the effects of age and sex as possible cofactors. Twenty-one studies containing data from interventions conducted between 1997 to 2019 and published between 2008 and 2021with 3153 patients (68.5% male) were included. ET was applied to 1693 patients (53.7%) and FET to 1460 (46.3%). Overall mortality after ET was 250/1693 (14.8%) and after FET 116/1460 (7.9%). Relative risk (RR) and 95% confidence interval (CI) were 1.37 [1.04-1.81], p=0.027. There was no significant effect of age and sex. SCI occurrence after the second stage of ET was 45/1693 (2.7%) and after FET 70/1460 patients (4.8%). RR 0.53 [0.35-0.81], p=0.004. Age and sex were not associated with the risk of SCI. No significant differences were observed between ET and FET in the incidence of stroke and renal failure. Our results indicate that ET is associated with higher early mortality but lower incidence of SCI compared to FET. When studies published in the last 5 years were analyzed, no significant differences in mortality or SCI were found between ET and FET. This difference is attributed to a decrease in mortality after ET, as the mortality after FET did not change significantly over time.